The Party in Krzysztof Kieślowski’s Films - Zwierzchowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Probably no other Polish filmmaker has devoted as much attention to the Polish United Workers’ Party (PZPR) as Krzysztof Kieślowski did in his films. Early on, he perceived the party as an organization where one could meet people with different desires, motivations and modus operandi. Kieślowski’s perspective could be defined as such: do not judge the whole, focus on individuals. His subsequent films present a change in this perspective. Workers and devoted members of the communist party were in the center of the director’s interest in some of his early films. Later, he focused more and more on individuals, especially those who had to face the party as a structure and hierarchy. Kieślowski’s films made in the early 1980s show party leaders and people in charge who eventually turn out to be losers. Kieślowski perceived various aspects and forms of being a party member, not only as a stepping stone for one’s career. He saw and presented the everyday life of PZPR, relations between the authorities and society, and its members and representatives of the party apparatus. He was quite critical about the party and people in charge, but also tried to see and present the reasons motivating their conduct. Social and political changes in Poland in the early 1980s made this kind of approach increasingly difficult for Kieślowski.